Friend of My Youth - Alice Munro (USA Vintage, 1991)
The ten miraculously accomplished stories in Alice Munro's Friend of My Youth not only astonish and delight but also convey the unspoken mysteries at the heart of all human experience.
Keywords: Fiction; Short Stories; Contemporary; Women; Classics